Exploring Factors Affecting Gender Disparities in Enrollment Patterns Within Technical Colleges: A Study Of Motor Vehicle Mechanic Trade In Gombe State - KUMAZHEGE, Stephen Z; UMAR, Hadiza (International Journal on Human-Computing Studies, 2023)
The study titled "Exploring Factors Affecting Gender Disparities in Enrollment Patterns Within Technical Colleges: A Study of Motor Vehicle Mechanic Trade in Gombe State" seeks to address the persistent gender disparities in enrollment within Technical Colleges, focusing specifically on the Motor Vehicle Mechanic Trade program in Gombe State. The study was guided by three research question and hypotheses. The total population for this study was 527 including administrators, teachers and parents of Motor Vehicle Mechanic Work trade students in Government Science and Technical Colleges in Gombe State. The sample size of the study was 116 determined using stratified random sampling.The methodology employs a descriptive survey research design within the context of Gombe State in Nigeria. Data was collected through a structured questionnaire developed by the researcher, focusing on teachers, school administrators, and parents. The collected data is analyzed using descriptive statistics, means, standard deviations, and ANOVA to address the research questions and test the hypotheses. The findings of the study reveal that both teachers' and school factors significantly influence female students' enrollment in the Motor Vehicle Mechanic Trade program. Additionally, various strategies are identified as potential enhancers of female enrollment. Recommendations include enhancing teacher training, establishing guidance and counseling services, creating supportive environments, employing female technical trainers, and providing targeted skill acquisition centers to promote and enhance female enrollment in the Motor Vehicle Mechanic Trade program.